Determinants of B2B Partnership Sustainability in the OYO Digital Hospitality Platform: The Role of Customer Relationship Management, Digital Promotion Strategy, and Price Fairness with Platform Reputation as a Moderating Variable - Dewi Indah Lestari; Ryan Kurniawan (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2026)
The rapid development of digital platforms has significantly transformed the structure of the hospitality industry. Digital hospitality platforms such as OYO, Airbnb, and Booking.com have created new business ecosystems where hotels rely heavily on platform intermediaries to access broader markets and improve operational efficiency. However, the sustainability of business-to-business (B2B) partnerships between hotels and platform providers remains a critical challenge, particularly in relation to relationship governance, pricing transparency, and promotional strategies. This study aims to analyze the determinants of B2B partnership sustainability between hotels and digital hospitality platforms by examining the roles of Customer Relationship Management (CRM), Digital Promotion Strategy, and Price Fairness Perception. In addition, the moderating role of Platform Reputation is investigated to understand how platform credibility strengthens or weakens these relationships. This research adopts a quantitative approach using an explanatory survey method. Data were collected from 170 hotel partners collaborating with OYO Rooms in Bandung, Indonesia. The respondents consisted of hotel owners, general managers, and operational managers who were directly involved in managing the partnership with the platform. The collected data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that Customer Relationship Management and Price Fairness Perception significantly influence B2B partnership sustainability. However, Digital Promotion Strategy does not have a significant direct effect on partnership sustainability. Furthermore, Platform Reputation strengthens the relationships between CRM, digital promotion strategy, and price fairness with partnership sustainability. These results highlight the importance of relational governance, fairness mechanisms, and institutional trust in maintaining sustainable partnerships within digital hospitality ecosystems. The study contributes to the literature on digital platform governance and B2B relationship management while providing managerial implications for improving collaboration between hospitality platforms and hotel partners